Preparation and Use of Turn-on Fluorescent Probe for Detection and Live Cell Imaging of Vitamin D Receptor as a Target Protein - Hiroyuki Kojima; Toshimasa Itoh (STAR Protocols, 2020)
SUMMARY: Turn-on fluorescent probe mediated by conjugate addition and cyclization (TCC probe) is a small molecule that reacts with a protein of interest in cells. TCC probe is applicable to various types of proteins by exchanging the ligand unit for target proteins. TCC probes are a potent tool for molecular imaging and chemical proteomics. This protocol describes the synthesis of a TCC probe via unstable intermediate and how to use this probe to visualize vitamin D receptor as a target protein.For complete details on the use and execution of this protocol, please refer to Kojima et al. (2020).